2016
DOI: 10.1186/s12890-016-0312-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of asthma in patients with primary Sjögren’s syndrome: a retrospective cohort study

Abstract: BackgroundSjögren’s syndrome (SS) has been associated with bronchial hyperresponsiveness and asthma; however, no population-based cohort study has been performed. We evaluated the risk of asthma in patients with primary SS in a nationwide population.MethodsWe conducted a retrospective cohort study using data from the National Health Insurance Research Database in Taiwan. The primary SS group included 4725 adult patients diagnosed between 2000 and 2006. Each patient was frequency-matched with four people withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(27 reference statements)
0
6
1
Order By: Relevance
“…In our study, the rates of asthma and AR in patients with pSS were 6%, and 10%, respectively. Our rates were lower than the rates of atopic diseases reported in the previous studies (18,19). This result may arise from the number of study population or differences in the study methods.…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, the rates of asthma and AR in patients with pSS were 6%, and 10%, respectively. Our rates were lower than the rates of atopic diseases reported in the previous studies (18,19). This result may arise from the number of study population or differences in the study methods.…”
Section: Discussioncontrasting
confidence: 85%
“…NOD mice are genetically prone to immune dysregulation, which promotes multiorgan autoinflammation and allergy . Studies have shown that human subjects with autoimmune disorders are more susceptible to allergy . Additionally, the association of innate immunity with genetic makeup, such as C57BL/6 vs NOD, is not known, and there has not been a published study on the CHS response in NOD mice; to our knowledge, our current study is the first investigation in the literature.…”
Section: Discussionmentioning
confidence: 89%
“…26,27 Studies have shown that human subjects with autoimmune disorders are more susceptible to allergy. [28][29][30] Additionally, the association of innate immunity with genetic makeup, such as C57BL/6 vs NOD, is not known, and there has not been a published study on the CHS response in NOD mice; to our knowledge, our current study is the first investigation in the literature. Thus far, most CHS studies in the literature used mice on the C57BL/6 background.…”
Section: Discussionmentioning
confidence: 97%
“…In a cohort of 4,725 adults with SS matched with controls, the incidence of asthma was 1.62-fold higher in subjects with SS. 188 In a cohort of 3,013 women with SS, there was a 1.4-fold greater incidence of COPD than in matched controls. 189 In a smaller cohort study assessing COPD in 51 consecutive subjects with pSS, 41% had COPD based on Global Initiative of Chronic Obstructive Lung Disease (GOLD) criteria, including 30% of the nonsmokers with pSS.…”
Section: -27%mentioning
confidence: 99%